Affordances for Motor Skill Development in Home, School, and Sport Environments - Flôres, Fábio Saraiva (2019)
Through development, a child’s varied movement contexts provide different opportunities or affordances for action that are fundamental to promoting motor competence. Although home is the primary environment for infants, as children age, school and sport environments gain importance. Studies focusing on affordances for motor behavior in children have mainly addressed the home microsystem, providing an incomplete picture of affordances across different settings, particularly later in development. Here, we undertook a narrative literature review of various affordances for children’s motor development. This review revealed that prior studies of school and sports contexts have not specifically focused on those environmental properties that promote or hinder motor learning opportunities, meaning that future research should assess these relationships through manipulations of environmental features in these different microsystems.